A comparative study on the production of extracellular hydrolytic enzymes of C. albicans and non-albicans Candida species isolated from HIV+/AIDS patients and healthy individuals - Mahnaz Fatahinia; Ali Zarei Mahmoudabadi; Fatemeh Fathi (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Oropharyngeal candidiasis is the most prevalent opportunistic fungal infection in patients with human immunodeficiency virus (HIV) as well as other immunodeficiency disorders, which is caused by various Candida species,mostly Candida albicans. Studies have shown that Candida isolates differ in their pathogenicity. These variations are attributed to virulence factors, host characteristics, and the target tissue. This study aimed to determine and compare the secretion of hydrolytic enzymes in C. albicans and non-albicans Candida species isolated from HIV+/AIDS patients and healthy individuals.Materials and Methods: Samples were taken from 201 patients with HIV and 118 healthy individuals. The samples were identified by macroscopic, phenotypic, and molecular methods, and virulence factors were subsequently measured. Statistical differences in enzymatic activity of various Candida isolates were calculated (P<0.0001).Results: In total, 95 samples (47.20%) from patients and 46 samples (38.90%) from healthy individuals were positive for the growth of different Candida species. There were 39 (41.10%) and 36 (78.30%) C. albicans in patients and healthy individuals, respectively, as well as 56 (58.90%) and 10 (21.70%) non-albicans species in patients and healthy subjects, respectively. All the enzymes produced by Candida species enzymes were at low, medium, and high levels. Hemolysin activity in Candida species isolated from patients was significantly higher, compared to healthy individuals.Moreover, the activity of all C. albicans enzymes in patients was significantly higherthan other Candida species.Conclusion: The C. albicans isolated from HIV-positive individuals secreted higheramounts of exoenzymes, and can cause oropharyngeal candidiasis and become a sourceof candidiasis for the host.